Designing a Video Script of New Ocarina as One of Tourism Destination in Batam - Viranda, Syamarah Humairo (Politeknik Negeri Sriwijaya, 2024)
ABSTRACT: The aim of this research was to know how to design a video of New Ocarina as one of tourism destination in Batam using the steps of writing a script by Hanifa (2013). The methodology of this research was Research and Development Method (R&D) adapted from Plomp (1997). The steps were: (1) Preliminary Investigation, (2) Designing, (3) Realization/Construction, (4) Test, evaluation, and revision, (5) Implementation. In the preliminary investigation, the writer did a literature study and field study. In designing, the writer designs the script using Jakacaping (2018) format. Then, there is realization/construction. In this step the writer make first draft. After that, the writer did testing, evaluation, and revision by gave it to 5 experts. The experts were evaluating and giving comments to the script and video. After that the writer revised the script and the video. In conclusion the writer could make a script that has been testified by using Hanifa (2013) of steps writing script and research and methodology by Plomp (1997). Keywords: Video, Script, Tourism destination